KRITIK SASTRA MELALUI PANDANGAN FEMINISME DALAM NOVEL SI CANTIK DAN SANG PEMBERANI KARYA ATIKAH SOLIHAH - Mulasih; Sulistiyono; AR, Muhammad Misbahudholam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The modern world requires a wider perspective in life, one of which is about feminism which is a representation of gender equality, more specifically to fight discrimination against women. This study was used to examine one of children's book entitled,